A taxonomic revision of the Neotropical termite genera Labiotermes Holmgren and Paracornitermes Emerson (Isoptera: Termitidae: Nasutitermitinae) - Constantino, Reginaldo (2006)
The taxonomy of the South American termite genus Labiotermes Holmgren (sensu novo) is revised,including identification keys to soldiers and workers, and distribution maps for all 10 species.Paracornitermes Emerson is treated as a new synonym of Labiotermes. Two new species aredescribed: L. guasu, from the Amazon rain forest and L. oreadicus, from the Cerrado of centralBrazil. Paracornitermes caapora Bandeira & Cancello and P. hirsutus Araujo are placed under thesynonymy of L. orthocephalus. The imagos of L. emersoni and L. orthocephalus are described forthe first time. The workers of all species are described and illustrated, including the enteric valve armature and the mixed segment. The soldiers of the species previously included inParacornitermes are redescribed.